2018
DOI: 10.1136/bjsports-2018-099218
|View full text |Cite
|
Sign up to set email alerts
|

Overuse injuries are prevalent in children’s competitive football: a prospective study using the OSTRC Overuse Injury Questionnaire

Abstract: ISRCTN14046021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 47 publications
5
55
1
3
Order By: Relevance
“…The Oslo Sports Trauma Research Center questionnaire on health problems was used to collect data (Clarsen et al, 2013(Clarsen et al, , 2014, which includes four questions on the consequences of health problems on sports participation, training volume, sports performance, and perceived pain. This questionnaire and methods have been reported to be used with success in population of youth athletes in elite junior tennis (Pluim et al, 2016), in adolescent elite orienteerers (Von Rosen et al, 2016), in youth football players (Leppänen et al, 2019), in junior handball players (Aasheim et al, 2018), and in youth elite athletes in multiple sports (Moseid et al, 2018), and appears of interest in sports who have limited access to medical personnel (e.g., athletics; Leppänen et al, 2019). Questionnaire responses were reviewed and collated on a weekly basis by the Athletics Ireland Physiotherapist.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The Oslo Sports Trauma Research Center questionnaire on health problems was used to collect data (Clarsen et al, 2013(Clarsen et al, , 2014, which includes four questions on the consequences of health problems on sports participation, training volume, sports performance, and perceived pain. This questionnaire and methods have been reported to be used with success in population of youth athletes in elite junior tennis (Pluim et al, 2016), in adolescent elite orienteerers (Von Rosen et al, 2016), in youth football players (Leppänen et al, 2019), in junior handball players (Aasheim et al, 2018), and in youth elite athletes in multiple sports (Moseid et al, 2018), and appears of interest in sports who have limited access to medical personnel (e.g., athletics; Leppänen et al, 2019). Questionnaire responses were reviewed and collated on a weekly basis by the Athletics Ireland Physiotherapist.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…This purpose-built instrument was devised in 2013 17 and updated in 2020 15 and has played an increasing role in sports injury and illness surveillance, especially in sports and settings where overuse injuries and illnesses represent a substantial burden on health and performance. 71 The tool (which can be delivered via a mobile application) invites athletes to record reduced sports participation, training modifications, performance reductions, and symptoms. 17 Based on the response to these questions, researchers can calculate a severity score ranging from 0 to 100 at specific time points.…”
Section: Athlete-reported Symptoms and Consequencesmentioning
confidence: 99%
“…The number of days that have elapsed from the date of injury to the date of the player's return to full participation in team training and availability for match selection 42 Injury incidence should preferably be described as the number of injuries per 1000 player-hours (h) rather than the number of injuries per athlete-exposure (AE), since the duration of the latter may vary 42 . The prevalence of injuries has only been described in a few studies and one study calculated the weekly prevalence of overuse injuries as the number of players reporting a problem divided by the total number of players in the same study week 87 . The overall injury rates in children's and youth football varies from two to seven injuries per 1000 hours of football in different studies, with higher injury rates during matches than during training as the players grow older 33 , (also see Table 1).…”
Section: Injury Surveillancementioning
confidence: 99%
“…Younger players had more fractures and injuries to the upper body, whereas muscle/tendon strains and joint/ligament sprains were less common than in players over 14 33 . During a 20week-duration study of children's football (mean age 12 years), almost 50% of all players reported overuse problems at least once during the study, and 31% reported a substantial overuse problem (leading to moderate or severe training volume or performance reductions) with a mean duration of almost four weeks 87 . A study of female youth football showed a rate of lower extremity overuse injuries of 1.9 per 1000 hours, with knee injuries being the most prevalent 128 .…”
Section: Injury Surveillancementioning
confidence: 99%
See 1 more Smart Citation